2019
DOI: 10.1111/1462-2920.14507
|View full text |Cite
|
Sign up to set email alerts
|

Microbial interactions in the anaerobic oxidation of methane: model simulations constrained by process rates and activity patterns

Abstract: Summary Proposed syntrophic interactions between the archaeal and bacterial cells mediating anaerobic oxidation of methane coupled with sulfate reduction include electron transfer through (1) the exchange of H2 or small organic molecules between methane‐oxidizing archaea and sulfate‐reducing bacteria, (2) the delivery of disulfide from methane‐oxidizing archaea to bacteria for disproportionation and (3) direct interspecies electron transfer. Each of these mechanisms was implemented in a reactive transport mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 83 publications
(223 reference statements)
1
20
0
Order By: Relevance
“…No flux conditions were imposed at the anode surface, where Cytred was converted to Cytox at a rate set by Jc, representing the offloading of electrons to electrode. 10 -14 -10 -16 (6×10 -15 ) Cell-specific acetate consumption rate constant Estimated from [6] μ d -1 varied Cell growth rate Calculated using Eq (1) ρ gdw cell -1 9.5×10 -14 Biomass density Estimated from [115] YAc gdw mol-Ac -1 4.32 Growth yield Calculated using Eq (3)…”
Section: Model Implementationmentioning
confidence: 99%
“…No flux conditions were imposed at the anode surface, where Cytred was converted to Cytox at a rate set by Jc, representing the offloading of electrons to electrode. 10 -14 -10 -16 (6×10 -15 ) Cell-specific acetate consumption rate constant Estimated from [6] μ d -1 varied Cell growth rate Calculated using Eq (1) ρ gdw cell -1 9.5×10 -14 Biomass density Estimated from [115] YAc gdw mol-Ac -1 4.32 Growth yield Calculated using Eq (3)…”
Section: Model Implementationmentioning
confidence: 99%
“…Not only do SO 42‐impacted environments have the most urgent need for clarifying the impact of S on overall wetland biogeochemistry, but they also provide the clearest test bed for examining S cycling in freshwater sediments. Previous reactive transport models have included AOM coupled to SO 42 reduction for marine environments (see review by Regnier et al, , and He et al, ), but similar applications in freshwater ecosystems are minimal. Additionally, uncertainties about specific mechanisms and their rates have limited the incorporation of “cryptic” S cycling in any model applications.…”
Section: Introductionmentioning
confidence: 99%
“…These features suggest that DIET is the principal mechanism of sulfate-dependent AOM. While this hypothesis awaits direct experimental confirmation or indirect support through measurements that show the potential for conduction within the aggregates and is hampered by a lack of any pure cultures of microorganisms carrying out this metabolism, modeling efforts indicated that DIET can support cell-specific AOM rates and archaeal activity distributions that were consistent with observations from single-cell resolved fluorescent in situ hybridization-nanoscale secondary ion mass spectrometry (FISH-nanoSIMS) analyses (19).…”
mentioning
confidence: 78%
“…Furthermore, direct interspecies extracellular electron transfer (DIET) has been observed in cocultures (10,11) and microbial aggregates (12)(13)(14)(15)(16). There is also a growing body of evidence that DIET also takes place between methanotrophic archaea and syntrophic sulfate-reducing bacteria in AOM consortia (17)(18)(19), where it serves as an effective transport mechanism over long spatial distances (17). It overcomes limitations inherent in the diffusive exchange of dissolved electron-carrying molecules (mediated interspecies electron transfer, or MIET) that lead to the build-up of reaction products and the subsequent shutdown of metabolic activity (19,20).…”
mentioning
confidence: 99%